Heart rate variability biofeedback as a strategy for dealing with competitive anxiety: A case study - Lagos, L.; Vaschillo, E.; Vaschillo, B.; Lehrer, P.; Bates, M.; Pandina, R. (Biofeedback, 2008)
Heart rate variability (HRV) biofeedback (BFB) is a relatively new approach for helping athletes to regulate competitive stress. To investigate this phenomenon further, a qualitative case study examined the impact of HRV BFB on the mood, physiology, and sport performance of a 14-year-old golfer. The golfer met once per week at a university lab for 10 consecutive sessions of HRV BFB training that included breathing at a frequency of 0.1 Hz. The format and duration of sessions followed the HRV BFB protocol outlined previously by Lehrer, Vaschillo, and Vaschillo. Acute increases in total HRV, low-frequency HRV, and amplitude of oscillation at 0.1 Hz were observed during biofeedback practice. This effect became stronger across sessions, suggesting increases in baroreflex gain. Following HRV BFB, the golfer achieved his personal record score for 18 holes of golf, and his mean golf score (total number of shots per 18 holes of golf) was 15 shots lower than in his previous golf season. The golfer received no golf instructions during HRV BFB training. The results of this case study suggest that HRV BFB training may help the athlete cope with the stress of competition and/or improve neuromuscular function